PENGURANGAN RISIKO BENCANA MELALUI PENGEMBANGAN MASYARAKAT TANGGUH BENCANA DI DESA KEPUHARJO, KECAMATAN CANGKRINGAN - , Fitri Oknaini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kepuharjo Sub District in Cangkringan District is one of the sub district in Sleman Regency which directly adjacent to Mount Merapi. Located nearby Mount Merapi and passed by Gendol River and Opak River causing this area has a high vulnerability to phiroclastic flows hazard of Mount Merapi. The aims of this research are to determine the spatial pattern of risk in study area, to find out the community circumstances in study area, and to arrange the strategy in development of disaster resilient communities in study area. The method used in this research is qualitative-inductive method by collecting fact on study area to build theories about disaster resilient communities. The technique to compiling data are survey and in-depth interviews using purposive sampling method. Also conducted focus group discussion (FGD) to compile the ideas about strategy for strenghtening the capacity to establish disaster resilient communities. The result of this research indicate that 42,51 % of the study area has a high vulnerability, 8,00 % has moderate vulnerability, and 49,48 has low vulnerability. Risk analysis shows that four site in study area have a high level of risk of 343 ha, three site in study area have a medium level of risk of 262 ha, and one site in study area has a low level of risk. After 2010 eruption, the condition of community change both physically, economically, and socially. Settlement pattern and livelihood are changing, as well as increase in knowledge and public awareness about the disaster. On the other hand there are problems about evacuation road and lack of preparation in the face of disaster. There are some ideas about development strategy of disaster resilient communities that obtained from interviews and FGD to increase capacity and reduce vulnerability. The strategy is devided into three, the first is strategy before disaster, the second is strategy in disaster response, and the third is strategy post disaster.